Management of periorbital basal cell carcinoma with orbital invasion. (November 2015) - Sun, Michelle T; Wu, Albert; Figueira, Edwin; Huilgol, Shyamala; Selva, Dinesh
Basal cell carcinoma (BCC) is the most common eyelid malignancy; however, orbital invasion by periocular BCC is rare, and management remains challenging. Established risk factors for orbital invasion by BCC include male gender, advanced age, medial canthal location, previous recurrences, large tumor size, aggressive histologic subtype and perineural invasion. Management requires a multidisciplinary approach with orbital exenteration remaining the treatment of choice. Globe-sparing treatment may be appropriate in selected patients and radiotherapy and chemotherapy are often used as adjuvant therapies for advanced or inoperable cases, although the evidence remains limited. We aim to summarize the presentation and treatment of BCC with orbital invasion to better guide the management of this complex condition.